2009
DOI: 10.1038/nprot.2009.155
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic hydrogel molding to control the 3D geometry of bioartificial muscle tissues

Abstract: This protocol describes a cell/hydrogel molding method for precise and reproducible biomimetic fabrication of three-dimensional (3D) muscle tissue architectures in vitro. Using a high aspect ratio soft lithography technique, we fabricate polydimethylsiloxane (PDMS) molds containing arrays of mesoscopic posts with defined size, elongation and spacing. On cell/hydrogel molding, these posts serve to enhance the diffusion of nutrients to cells by introducing elliptical pores in the cell-laden hydrogels and to guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
188
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 199 publications
(193 citation statements)
references
References 50 publications
1
188
2
Order By: Relevance
“…Large single muscle bundles and smaller tribundle muscle implants were formed within polydimethylsiloxane (PDMS) molds as previously described (26,41). Cell/hydrogel mixture (SI Appendix, Table S1) was injected into the PDMS molds, polymerized at 37°C for 45 min, and cultured on a rocker at 37°C for up to 4 wk.…”
Section: Methodsmentioning
confidence: 99%
“…Large single muscle bundles and smaller tribundle muscle implants were formed within polydimethylsiloxane (PDMS) molds as previously described (26,41). Cell/hydrogel mixture (SI Appendix, Table S1) was injected into the PDMS molds, polymerized at 37°C for 45 min, and cultured on a rocker at 37°C for up to 4 wk.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Bian et al developed a soft lithography protocol to seed a mixture of muscle cells and fibrin gel within a poly(dimethyl siloxane) (PDMS) mold, creating www.advancedsciencenews.com www.advhealthmat.de a muscle tissue sheet with elliptical pores that improved the directionality within the muscle fibers (Figure 6). [130] Similarly, Gauvin et al used a 3D projection stereolithography technique to form a macroporous gelatin methacrylate hydrogel structures for cell growth and tissue engineering applications. [131] Weidner and co-workers have also shown that templated microchanneled/capillary hydrogels fabricated through 3D projection stereolithography are effective as anisotropic scaffolds for promoting axonal regrowth.…”
Section: Wwwadvancedsciencenewscom Wwwadvhealthmatdementioning
confidence: 99%
“…20,21 The use of computer-assisted design to systematically alter tissue mold dimensions and introduce tissue pores with defined geometry, distribution, and direction in this system allowed us to precisely control engineered tissue thickness, shape, and local and global alignment of differentiated muscle fibers. Specifically, by fabricating elastomeric tissue molds with parallel hexagonal posts arranged in staggered fashion, we were able to create fibrin gel-based muscle networks containing: (1) elliptical pores with length that was directly determined by the post length (PL) and width that was determined by both the post width and degree of cell-mediated gel compaction, and (2) dense, cross-striated myofibers that were in average aligned along the long axis of the elliptical pores.…”
Section: Introductionmentioning
confidence: 99%